Community-based breeding programs – a sustainable way to improve small ruminant production in developing countries - M, Kousalya Devi; R, Narayan; S, Durga; R, Venkataramanan (Indian Farming, 2020)
Community based breeding programs are proposed as an option for genetic improvement of livestock in developing countries. The aim is not to blindly adopt breeding programs from the temperate countries, but to ensure designing and handling of breeding program by and for the community for a sustainable development in developing countries. Understanding the community’s practice and preference on selection of sheep, ram sharing and management; and incorporating knowledge of genetic parameters (heritability and correlation) are the main determinants for design of community-based breed improvement program. This approach has been a promising model in many countries, however, the present guidelines will have to be refined according to each community and updated as experience accumulates and our tools improve.